МОЙЛИ ХОМ АШЁЛАРНИНГ НОАНЪАНАВИЙ ТУРЛАРИДАН ОЛИНГАН МОЙЛАРДАН ФУНКЦИОНАЛ ПАРҲЕЗБОП ИСТЕЪМОЛ МОЙЛАРИ ИШЛАБ ЧИҚАРИШДАГИ АХАМИЯТИ - Саидов Абди; Утаева Гузал Нурбаевна (Journal of new century innovations, 2024)
Abstract: In recent years, the problem of maintaining human health due to environmental deterioration has become a threat, and the development of new functional properties with preventive and therapeutic properties, using biologically active substances with any biologically active substances, has created the need to develop a change in the qualitative and quantitative composition of the diet. nutrition of the population.